Light Scattering Flow Cytometry for the Detection and Monitoring of Circulating Cancerous Cells - Lyons, Joseph. (2017)
Abstract: Detection of circulating cancer cells is of major importance to epithelial and blood based cancers. In epithelial cancers, the presence of circulating tumor cells (CTC) correlates with metastatic burden and shortened overall survival. For lymphoma, a cancer of the blood and lymph nodes, relapse is thought to be caused by residual lymphoma cells hiding in bone marrow and lymph node microenvironments (ME). Quantifying the number of lymphoma cells entering circulation would be a direct measure of drug efficacy and provide a means to assess individual chemotherapy treatment. The objective of this thesis was to assess the potential to use microfluidic confocal flow cytometry to discriminate cancerous cells from white blood cells based on differences in backscattered light at different wavelengths. In particular, backscatter flow cytometry's utility in an in-vitro lymphoma model, and breast cancer mouse model was assessed.; Thesis (M.S.)--Tufts University, 2016.; Submitted to the Dept. of Biomedical Engineering.; Advisor: Irene Georgakoudi.; Committee: Irene Georgakoudi, Andreas Klein, and Qiaobing Xu.; Keywords: Biomedical engineering, and Optics.